2020
DOI: 10.3390/ijerph17145121
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rates of Loneliness and Its Impact on Lifestyle in the Healthy Population of Madrid, Spain

Abstract: Background: The Spanish population presents higher levels of loneliness than citizens of countries in Northern Europe. Numerous studies have linked loneliness to increased morbidity and mortality, but very few studies have associated loneliness with healthy lifestyles. The objectives of this research are to identify the feeling of unwanted loneliness in various age and gender groups in the city of Alcalá de Henares (Madrid, Spain), to determine lifestyle habits in the areas of diet and physical exercise, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Self-reported information on health behaviors was derived from the surveys. These covariates included smoking status (daily smokers, occasional smokers, former smokers, and non-smokers), physical activity (physically active vs physically inactive), weekly alcohol consumption (no intake, low/moderate consumption 1–141–21 drinks/week for women (men) and high consumption >14 (>21) drinks/week for women (men)), and the intake of salad on a weekly basis, which was used as a proxy of dietary habits (every day/several times a day, occasionally, and never/rarely). Further, self-reported height (cm) and weight (kg) were used to calculate respondents’ body mass index (BMI), which was classified as underweight (BMI<18.5 kg/m 2 ), normal weight (BMI≥18.5–24.9 kg/m 2 ), overweight (BMI≥25–29.9 kg/m 2 ), obesity (BMI≥30–39.9 kg/m 2 ), and severe obesity (BMI≥40 kg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-reported information on health behaviors was derived from the surveys. These covariates included smoking status (daily smokers, occasional smokers, former smokers, and non-smokers), physical activity (physically active vs physically inactive), weekly alcohol consumption (no intake, low/moderate consumption 1–141–21 drinks/week for women (men) and high consumption >14 (>21) drinks/week for women (men)), and the intake of salad on a weekly basis, which was used as a proxy of dietary habits (every day/several times a day, occasionally, and never/rarely). Further, self-reported height (cm) and weight (kg) were used to calculate respondents’ body mass index (BMI), which was classified as underweight (BMI<18.5 kg/m 2 ), normal weight (BMI≥18.5–24.9 kg/m 2 ), overweight (BMI≥25–29.9 kg/m 2 ), obesity (BMI≥30–39.9 kg/m 2 ), and severe obesity (BMI≥40 kg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The biological pathway is related to metabolic mechanisms increasing the risk of obesity and the metabolic syndrome, both of which are associated with loneliness14 and type 2 diabetes 15. The second pathway suggested is through adverse health behaviors, although research related to loneliness has yielded inconsistent results 8 16–18. Lastly, the third pathway is the psychological pathway.…”
Section: Introductionmentioning
confidence: 99%
“…This longevity shown by statistics is redefining the roles and image of older people in many countries, and could be considered as a great challenge for social and health systems, in terms of increase of chronic diseases, dependence and psychosocial consequences, such as loneliness and mental health problems. Loneliness and lack of social support have been found to be high in Spanish older people [ 2 , 3 ]. For example, Tan et al showed that 36,7% of Spanish older people reported loneliness, and Cuesta-Lozano et al found that 83.33% of adults aged 65 years or older reported some degree of loneliness [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness and lack of social support have been found to be high in Spanish older people [ 2 , 3 ]. For example, Tan et al showed that 36,7% of Spanish older people reported loneliness, and Cuesta-Lozano et al found that 83.33% of adults aged 65 years or older reported some degree of loneliness [ 2 , 4 ]. Some cultural aspects (the importance of family and friends and having a close contact with them), have been suggested as an explanation for these figures.…”
Section: Introductionmentioning
confidence: 99%